THE RELATIONSHIP BETWEEN BODY IMAGE AND ADOLESCENT MENTAL HEALTH IN MANADO, INDONESIA: A CROSS-SECTIONAL STUDY - Onibala, Bulan Nada Stevina; Nisa, Khairun; Simanjuntak, Susi Roida (Journal of Community Mental Health and Public Policy, 2026)
Background: Adolescence is a crucial period of transition marked by physical, emotional, and social changes that make individuals more vulnerable to developing a negative body image. Dissatisfaction with body image can cause problems, such as mental health. Purpose: This study aimed to analyze the relationship between body image and the mental health of adolescents at SMAN (Senior High School) 1 Manado. Methods: This study was a cross-sectional study involving 315 students selected using the Proportionate Stratified Random Sampling technique on students of SMAN 1 Manado. The measuring instruments used were the Body Shape Questionnaire-34 (BSQ-34) with a validity value of 0.826–0.902 and a reliability of 0.990 and the General Health Questionnaire-12 (GHQ-12) with a reliability value of 0.841 and proven valid with a LR+ value of 2.12 and LR– of 0.31. The analysis used in this study was the Spearman test. Results: The results showed a positive relationship between body image and mental health among adolescents (p = 0.000; r = 0.241). Conclusion: Body image is positively associated with adolescents’ mental health, indicating that adolescents with a more positive body image tend to have better mental health conditions; Therefore, interventions promoting self-acceptance and a healthy body image are essential for mental health promotion and prevention. Abstrak Latar belakang: Masa remaja adalah masa transisi dan eksplorasi. Pada tahap ini, perubahan fisik, emosional, dan sosial yang signifikan membuat remaja lebih rentan mengalami body image negatif. Ketidakpuasan terhadap body image tersebut dapat menimbulkan masalah, seperti kesehatan mental. Tujuan: untuk menganalisis hubungan antara body image dengan kesehatan mental remaja di SMAN 1 Manado. Metode: Penelitian ini merupakan Cross Sectional Study pada siswa SMAN 1 Manado. Teknik sampling yang digunakan adalah Proportionate Stratified Random Sampling dengan besar sampel sebanyak 315 siswa. Alat ukur yang digunakan adalah Body Shape Questionnaire-34 (BSQ-34) dengan nilai validitas 0,826–0,902 serta reliabilitas sebesar 0,990 dan General Health Questionnaire-12 (GHQ-12) dengan nilai reliabilitas 0,841 serta terbukti valid dengan nilai LR+ sebesar 2,12 dan LR– sebesar 0,31. Analisis yang digunakan dalam penelitian ini adalah uji spearman. Hasil: Hasil dari penelitian ini menunjukan adanya hubungan positif antara body image dengan kesehatan mental pada remaja (p = 0,000), dengan nilai r = 0,241. Kesimpulan: Body image memiliki hubungan terhadap kesehatan mental remaja dengan arah hubungan positif, di mana remaja yang memiliki body image lebih positif cenderung menunjukkan kondisi kesehatan mental yang lebih baik, sehingga perlu adanya intervensi mengenai penerimaan diri dan citra tubuh yang sehat sebagai bagian dari upaya promotif dan preventif dalam menjaga kesehatan mental remaja.